Wilson’s Disease Presenting With Haematuria and Swelling (Journal of Chittagong Medical College Teachers' Association, 2012)
Wilson’s disease gene located in Chromosime 3 is also expressed in Kidneys. So Wilson’s disease may have renal manifestations either as primary even or secondarily as Hepato renal syndrome. Patients commonly manifest as Fanconi syndrome or Urolithiasis. Haematuria and proteinuria is a rare manifestation. Here we are presenting a case who initially presented with haematuria and proteinuria (Acute nephritic syndrome) which masked features of Wilson’s disease and late diagnosis.JCMCTA 2012; 23(1): 51-52